Predicting climate impacts to the Olympic Games and FIFA Men's World Cups from 2022 to 2032 - Ross, Walker J.; Orr, Madeleine (Sport in society, 2022)
In response to concern for climate change impacting sport competitions and legacies, and the need to consider climate adaptability in event planning, this paper uses a combination of historical weather and air quality data as well as the Intergovernmental Panel on Climate Change Fifth Assessment Report to predict climactic conditions for the mega-events of the 2022 through 2032. In doing so, this paper provides a preliminary overview of environmental conditions (e.g. temperatures, air quality, precipitation) that can be used by event planners to inform contingency plans for the events and their legacies. The most immediate concerns for the mega events between 2022 and 2032 include heat conditions unsuitable for competition and poor air quality, but there may be more harmful environmental concerns for the long-term legacies of these events. It is imperative that event organizers consider creating climate-resilient events, infrastructure, and legacies that can withstand environmental threats in the future.